2010
DOI: 10.2139/ssrn.1705207
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Contributions of Behavioral Economics and Other Social Sciences in Understanding Taxation and Tax Reform

Abstract: This paper extends previous work presented at the SABE/IAREP conference at St Mary's University, Halifax (James, 2009). In the earlier paper it was shown that conventional economic theory is used to make the case for tax reform but does not always adequately incorporate all the relevant factors. However, an approach based on behavioral economics can make the difference between success and failure. In this paper the contributions of other social sciences are also included. Taxation is a particularly appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…James S. [11] showed that an approach based on behavioral economics and social sciences can be applied successfully to study taxation and tax reforms, in particular the influence of different factors on tax behaviour.…”
Section: Literature Review 21 Research On the Factors Of Tax Evasionmentioning
confidence: 99%
“…James S. [11] showed that an approach based on behavioral economics and social sciences can be applied successfully to study taxation and tax reforms, in particular the influence of different factors on tax behaviour.…”
Section: Literature Review 21 Research On the Factors Of Tax Evasionmentioning
confidence: 99%